The Effect of Training and Career Management Through the Mediating Role of Organizational Commitment To The Performance of Hospital Employees - Rusmana, Mey Irmayanti; Muhammad, Halifta; Firdaus, Erwin (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study aims to find out and analyze the influence of training and career management on the performance of employees of The Muhammadiyah Hospital Bandung, especially in the nursing division, but this research was carried out through intervening variability, namely organizational commitment. The research method used in this study used a quantitative approach by sampling using a random sampling technique from the total research population of 149 nurses. Then data collection was carried out using a research instrument in the form of a questionnaire measured on a likert scale. This study also conducted an analysis prerequisite test on the data that has been obtained, so that data that has met the requirements can be processed using multiple linear regression and analyzed using path analysis with the help of the SPSS Ver. 28 program. The findings show that the variables of training and career management have a positive and significant influence on the performance of nurses both directly and through the intervening variability of organizational commitments.